2015
DOI: 10.5223/pghn.2015.18.4.217
|View full text |Cite
|
Sign up to set email alerts
|

Early Life Factors Influencing the Risk of Obesity

Abstract: The obesity epidemic is a worldwide problem. Factors predisposing to obesity include genetics, race, socioeconomic conditions, birth by cesarean section, and perinatal antibiotic use. High protein (HP) content in infant formulas has been identified as a potential culprit predisposing to rapid weight gain in the first few months of life and leading to later obesity. In a large multicountry study the effects of lower protein (LP) formula (1.77 and 2.2 g protein/100 kcal, before and after the 5th month, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…We found that girls with AWG between 6 and 15 months of age had shorter exclusive and total breastfeeding times than did their peers. Our results were in accordance with the previous studies in which infant formulas were proposed to predispose them to AWG in infancy (38). In a recent study, Kale et al (39) reported that girls who were mixed-fed or predominantly breastfed had later onset of breast development than formula-fed girls, and that the duration of breastfeeding was directly related to the age at onset of breast development.…”
Section: Discussionsupporting
confidence: 93%
“…We found that girls with AWG between 6 and 15 months of age had shorter exclusive and total breastfeeding times than did their peers. Our results were in accordance with the previous studies in which infant formulas were proposed to predispose them to AWG in infancy (38). In a recent study, Kale et al (39) reported that girls who were mixed-fed or predominantly breastfed had later onset of breast development than formula-fed girls, and that the duration of breastfeeding was directly related to the age at onset of breast development.…”
Section: Discussionsupporting
confidence: 93%
“… 1 , 3 Childhood obesity may persist into adulthood, thereby contributing to widespread cardiometabolic comorbidities. 4–6 Beyond maternal obesity, 7 , 8 socioeconomic status, 9 , 10 and early life nutrition, 7 , 11–13 emerging evidence indicates that the infant gut microbiota may influence growth trajectories in the first year of life, 14–17 which may in turn predict future obesity. 3 , 18 , 19 Given that rapid infant growth is a potential determinant of overweight/obesity in school-age children, 20 the developing gut microbiota may be an important predictor for rapid infant growth and childhood obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Obesity may track throughout the life course and is associated with a myriad of conditions, including cardiovascular disease, type 2 diabetes, metabolic syndrome, joint problems, reduced life expectancy, and poorer psychological state . Obesity is a multifaceted disorder with an interplay among genetic, dietary, and hormonal factors contributing to its development early in life . As such, exposures during infancy may program metabolic health later in life, and prevention efforts could begin early.…”
Section: Introductionmentioning
confidence: 99%